Effects of fasting on appetite-regulating hormones and hearing function in adults with type 2 diabetes mellitus - Novita, Khuznita Dasa (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2025)
Background: Type 2 Diabetes Mellitus (T2DM) is known to affect multiorgan systems, including auditory function, with metabolic dysregulation playing a central role. Leptin and ghrelin, as metabolic hormones, are involved in energy homeostasis and neuroprotection, and may be influenced by fasting behavior. Objectives: This study aimed to explore the associations between fasting practices, serum leptin and ghrelin levels, and hearing function in adults with T2DM.Methods: A cross-sectional study was conducted involving 86 adults with T2DM, categorized into fasting (n=46) and non-fasting (n=40) groups. Serum leptin and ghrelin levels were measured using ELISA after an overnight fast. Hearing thresholds were assessed with pure-tone audiometry at 500, 1000, 2000, and 4000 Hz. Hearing loss was defined as a mean threshold >25 dB. Data were analyzed using Mann–Whitney U tests, Chi-Square tests, and logistic regression.Results: The fasting group had significantly lower leptin (32.85 ± 31.03 ng/mL vs. 40.89 ± 23.40 ng/mL, p=0.012) and ghrelin levels (5.48 ± 3.37 ng/mL vs. 7.32 ± 3.32 ng/mL, p<0.001). Hearing thresholds were slightly lower in the fasting group (20.80 ± 8.10 dB vs. 23.32 ± 11.13 dB), though the difference was not statistically significant (p=0.192). However, the frequency of hearing loss was significantly lower in fasting participants (21.7%) than in non-fasting participants (37.5%, p=0.015). Logistic regression revealed that higher leptin levels increased the risk of hearing loss (OR = 1.023, 95% CI: 1.004 - 1.042, p = 0.015), whereas fasting status was protective (OR = 0.429, 95% CI: 0.197 - 0.935, p = 0.033). Ghrelin, age, and sex were not significant predictors.Conclusion: Fasting may be associated with more favorable metabolic profiles and a lower frequency of hearing loss in individuals with T2DM. These findings suggest a potential protective role of structured fasting practices in auditory health, warranting further longitudinal studies to explore causality and underlying mechanisms.